Fucoidan Content in Philippine Brown Seaweeds - Narsico, Joemark T.; Nieva, Joyce A.; Alcaraz, Alper James G.; Anino V, Eladio G.M.; Gomez, Norchel Corcia F.; Montaño, Marco Nemesio E. (Science Diliman: A Journal of Pure and Applied Sciences, 2018)
This study aims to determine which brown macroalgae in the Philippines has the highest content of partially purif ied fucoidan. Percent fucoidan content of brown seaweeds Sargassum spp. , Padina sp. , Hydroclathrus sp. , Turbinaria ornata J. Agardh, Hormophyza cuneiformis PC Silva, and Dictyota dichotoma Lamouroux were determined in f ifty sites across 14 provinces in Northern Luzon (Cagayan, Ilocos), West Luzon (Pangasinan), the eastern seaboard of Luzon (Quezon Province, Camarines, Sorsogon), Central and Eastern Visayas (Bohol, Cebu, Negros Oriental, Negros Occidental), and Northern Mindanao (Camiguin, Lanao del Norte, Misamis Oriental, Misamis Occidental). Crude and semi-pure fucoidan were extracted through acid hydrolysis and ethanol precipitation using 50 grams of dried and milled seaweed biomass. Extracts were verif ied using infrared spectroscopy with fucoidan from Fucus vesiculosus as standard. Sargassum spp. is the most widely distributed source of fucoidan found in all sites. T. ornata was found in only 11 sites. Both have significantly higher percent content (p ≥ 0.05) of fucoidan than other sampled seaweeds. Higher percent content of semi-purified fucoidan were observed in D. dichotoma from Bohol (1.53%), H. cuneiformis from Cebu (2.17%), Hydroclathrus sp. from Pangasinan (2.23%), Padina sp. from Quezon Province (3.69%), Sargassum spp. from Camiguin (4.30%), and T. ornata from Cagayan (7.03%). Keywords: Brown seaweeds, distribution, fucoidan, fucoidan yield